An autonomous industrial robot for loading and unloading goods - Kadir, Md. Abdul; Chowdhury, Md. Belayet; Rashid, Jaber AL; Shakil, Shifur Rahman; Rhaman, Md. Khalilur (© 2015 Institute of Electrical and Electronics Engineers Inc., 2017)
This conference paper was presented in the International Conference on Informatics, Electronics and Vision, ICIEV 2015; Kitakyushu International Conference CenterFukuoka; Japan; 15 June 2015 through 18 June 2015 [© 2015 IEEE] The conference paper's definite version is available at: http://dx.doi.org/10.1109/ICIEV.2015.7333984